Etika Filsafat Dalam Meyikapi Over Religiusitas Pada Masyarakat Modern (Pendeketan Teori “Egoisme” Nietzsche) - Fauzan Akbar Novianto; Risladiba (Journal of Religion and Social Transformation, 2023)
In communal life, it is only fitting that as religious individuals, we should possess ethics and morals, as ethics and morals are taught in every religion. However, as time goes by, the values of ethics and morals have begun to fade in society due to the selfishness of people who prioritize themselves to secure a prominent position for themselves. Nietzsche has touched upon the selfish attitude of society in his theories such as Übermensch and Zarathustra, thus giving rise to Nietzsche's Ethical Egoism theory. By employing a literature review method and qualitative data analysis, the author attempts to dissect the issue of over-religiosity in society and seeks resolutions using Nietzsche's theories. Consequently, the solution to this issue is found in realizing the essence of religion itself, where believing in God and practicing religion should inherently involve ethics and morals. Additionally, understanding oneself as having extraordinary potential, everything should be critically examined and not easily controlled by others.